2006
DOI: 10.1210/jc.2005-2115
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma Resistin Level Is Associated with Enhanced Highly Sensitive C-Reactive Protein and Leukocytes

Abstract: Objectives: Resistin is a newly described hormone with a suggested role in insulin resistance. In humans, inflammatory cells seem to be the major source of resistin. The aim of this study was to find out whether plasma resistin concentration associates with carotid artery atherosclerosis and the risk factors of atherosclerosis.Methods: Plasma resistin concentrations were measured in 525 Finnish middle-aged subjects among our population-based cohort. Intima-media thickness was measured from the internal carotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
76
2
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 33 publications
17
76
2
6
Order By: Relevance
“…Consistent with some previous reports in Western (10,21) and Japanese populations (20) we found that women had higher resistin concentrations than men. However, this difference disappeared after adjustment for age, lifestyle factors, education status, geographic locations, family history of chronic disease, and uses of medications, suggesting that the gender difference of resistin levels could be explained by these factors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with some previous reports in Western (10,21) and Japanese populations (20) we found that women had higher resistin concentrations than men. However, this difference disappeared after adjustment for age, lifestyle factors, education status, geographic locations, family history of chronic disease, and uses of medications, suggesting that the gender difference of resistin levels could be explained by these factors.…”
Section: Discussionsupporting
confidence: 93%
“…However, studies on the association between resistin and chronic diseases in humans have yielded controversial results. Several studies showed that circulating resistin levels were associated with obesity (4-6), but this association was not found in others (7)(8)(9)(10). Although some studies have reported that resistin levels were higher in type 2 diabetic subjects than controls (8,11), other studies did not find any association between resistin and IR or fasting glucose levels (4,7,9,10,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] This finding was not supported by another study. 33 Resistin levels were also reported as not affected by age in adults.…”
Section: Introductioncontrasting
confidence: 76%
“…Previous studies of associations with resistin have been inconsistent not only with lipids and insulin resistance but also with obesity itself. [49][50][51][52][53][54][55] Hormone therapy has been shown to alter both leptin and adiponectin levels, and significant associations have been found between endogenous hormones and these adipokines. [56][57][58][59][60] However, to our knowledge, previous studies have not examined the role of menopause in the relationship between adipocytokines and CVD risk.…”
Section: Discussionmentioning
confidence: 99%